ICLEI Green Circular Cities Coalition : feasibility study to build an active network of circular economy actors in the Turku region - Silvonen, Essi; Kaskinen, Juha (fi=Turun yliopisto|en=University of Turku|, 2019)
The City of Turku and Finland Futures Research Centre have conducted a joint feasibility study to deter-mine the preconditions for the Turku region to take part in the Green Circular Cities Coalition initiated by ICLEI – Local Governments for Sustainability. Circular economy was examined through the six thematic sectors determined by ICLEI: urban spatial planning and governance, circular public procurement and supply chain, circular industrial park, municipal resource management, buildings and construction and water-food-energy nexus. Circular economy was recognised widely through the operations aimed at increasing resource efficiency and transitioning from a linear economy paradigm to a circular one, for example renewable energy sources, recycling, reuse, shar-ing platforms, bio economy and cleantech. Turku urban spatial planning has implemented circular economy solutions in its master plan by plan-ning new residential areas in old industrial areas located near the city centre and having access to public transportation. A more specific city plan requires construction companies to build circularity-advancing solutions, making the structure of the city denser and intensifying the implementation of life cycle assess-ment. Transportation and street planning are moving towards more environmentally neutral public trans-portation and sharing solutions for more efficient use of bikes and other vehicles. Green area planning has employed a new method called “blue-green factor” which determines the minimum amount of green areas in a property in relation to living areas. Stormwater directing solutions have also been intensified. Circular economy is a strong theme in the three spearhead projects of the City of Turku; Development of the city centre, Turku Science Park development and Smart and Wise Turku. On 11 June 2018, the Turku City Council approved the climate plan, which sets carbon neutrality by 2029 as the main target of its climate policy. Through the development work of its strategic entities, the City of Turku has been the local engine for advancing circularity. The general atmosphere towards climate actions among residents and officials of the city of Turku is positive, which is good, since a lot of partici-pation, solutions and work is required to reach the ambitious climate goals. Public procurement has the responsibility to set an example and the power to be a substantial influ-encer in developing corporate operations towards circularity. Challenges for advancing public procurement include tight legislation in tendering, lack of impartial quality criteria and follow-up systems and the low degree of readiness of circular economy products available on the market. The strategic procurement department of Turku is working with a “guide for sustainable procurement”, which aims to advance tender-ing quality criteria to support a sustainable procurement process. The main industrial fields of the Turku region are bio, ICT, marine and metal industries, construction and logistics, all with great potential for circular economy advancement. Bio-economy includes chemistry, medicine and food industries, agriculture and strong research in these fields. Turku Science Park Oy, a strategic entity of Turku, operates through its Clean team in innovation co-creation with local corporations, thus advancing industrial symbiosis. Turku University of Applied Sciences has a strong standing in circular economy business model creation and co-operation with local companies. Larger corporations have been aware of circularity and active in creating solutions for a long time. Smaller companies have less resources, but they are able to join circular operations through subcontracting. The municipal waste management of Turku is a joint solution of 17 municipalities with 12 waste centres and waste separation stations with Topinpuisto as the centre and showroom of circular economy. In 2021, a new ecological waste burning power plant will be opened in Salo, near Turku. A relevant field of action in the Turku area is textile recycling, which has been advanced through numerous projects. A pilot plant for textile recycling is being opened in Turku and the aim is to open a larger scale plant in the coming years. Approximately one third of greenhouse gas emissions is from buildings and construction, which gives them a central role in achieving the climate goals. Building circularity can be determined by the master plan and plot transfer clauses to some extent, which gives the city a substantial opportunity to guide con-struction company operations towards circularity. The city builds infrastructure and green areas in which the circularity of land masses is a considerable theme. The life cycle energy consumption of a building can be significantly affected through the planning and building phases. Circular solutions regarding existing buildings are improvement of energy efficiency, increasing the usage of space, making the life of a building longer through maintenance, renovation and restructuring or changing the purpose of use. End-of life-circularity considers how to circulate and reuse the building materials. The water-food-energy nexus is an internationally significant theme, since water is one of the most endangered resources and food and energy production are among the most polluting industrial sectors. The Turku region possesses substantial knowledge in the circular waste water purification system, which creates more energy than it consumes. Water-related themes are regionally strong through Baltic Sea protection and research. The Turku region is one of the centres of agriculture, food chains and food pro-duction, where research is strong and circularity is an important theme. The varieties cultivated in South-west Finland are very diverse, which also helps the area prepare for climate change. In energy production, the focus is on increasing renewable sources, utilising waste energy of industrial processes, energy stor-age and increasing energy efficiency solutions. Energy research is strong in the universities of the Turku area. As part of this feasibility study, the readiness of local actors to participate in the ICLEI GCCC co-operation was assessed. Most of the actors interviewed were interested. Some were even enthusiastic towards the co-operation, asserting that the contents need to be concrete and advance circular solutions in the Turku region. Turku possesses interesting contents in each thematic sector that can be included in the co-operation. Before the final selection of thematic sectors, it is important to discuss and agree with local actors, whether to select contents in which Turku is already strong or contents where Turku needs clear support from the network. Before conclusion it would also be interesting to communicate with other cities and find out what themes and which sectors they will bring to GCCC in order to create meaningful and influential co-operation.